Core Size Conversion of Au329(SCH2CH2Ph)84 to Au279(SPh‑tBu)84 Nanomolecules - Eswaramoorthy, Senthil Kumar; Sakthivel, Naga Arjun; Dass, Amala (Journal of physical chemistry. C, 2019)
We report the core size conversion of Au329(SCH2CH2Ph)84 to Au279(SPh-tBu)84 plasmonic nanomolecules. The mass spectrometric studies have revealed an unprecedented reaction pathway for the Au329 to Au279 core size conversion reaction via three steps. First, ligand exchange with 4-tert-butylbenzenethiolate occurs, followed by simultaneous progression of ligand exchange and core-size conversion with the loss of one Au atom after another and finally reaching completion with full ligand exchange on Au279. Typically, when a core size conversion occurs in molecule-like nanomolecules, different sizes have different electronic and structural properties; in this case, both the reactant and the product possess plasmonic behavior and bulk-like face-centered cubic structures. Also, this is the first report to study the core size transformation involving a difference of 50 metal atoms but identical 84 ligand count.